Harmonisasi Hukum atas Disparitas Putusan Mahkamah Agung dan Mahkamah Konstitusi - Walid Alfian; Erham; Amar Ma'arij (Jurnal Hukum Lex Generalis, 2025)
There is an overlapping authority between the Constitutional Court (MK) and the Supreme Court (MA) in reviewing laws and regulations. This is evident in the disparity between the Constitutional Court's decisions No. 70/PUU-XXII/2024 and No. 23P/HUM/2024 regarding the age limit for regional head candidates. The Constitutional Court uses the 1945 Constitution as a touchstone, while the Supreme Court uses the Law. This difference creates legal uncertainty. This study aims to analyze the Judicial Review authority of the Constitutional Court and the Supreme Court and formulate a harmonization strategy to avoid disparity in decisions. This study uses a normative legal method with a statutory and conceptual approach to examine the regulation and harmonization of Judicial Review in Indonesia. Harmonization efforts can refer to Law No. 13 of 2022, one of which is through the unification of normative review institutions.